2016
DOI: 10.1088/0268-1242/31/8/085002
|View full text |Cite
|
Sign up to set email alerts
|

Electric gating induced bandgaps and enhanced Seebeck effect in zigzag bilayer graphene ribbons

Abstract: We theoretically investigate effect of a transverse electric field generated by side gates and a vertical electric field generated by top/back gates on energy bands and transport properties of zigzag bilayer graphene ribbons (Bernal stacking). Using atomistic Tight Binding calculations and Green's function formalism we demonstrate that bandgap is opened when either field is applied and even enlarged under simultaneous influence of the two fields. Interestingly, although vertical electric fields are widely used… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 40 publications
3
15
0
Order By: Relevance
“…However, the outcome from group 3p + 1 is an exception since bandgap can even be enlarged (not reduced as in other semiconducting structures) under the effect of vertical electric fields. More interestingly, whereas transverse electric fields have been demonstrated to be more effective than vertical ones in BL-ZGNRs in terms of inducing larger bandgap, [27] here we show an inverse phenomenon, i.e., larger bandgap with vertical fields. In this present work, we consider BL-AGNRs in the presence of a transverse or/and a vertical electric field as schematized in Fig.…”
Section: Introductionsupporting
confidence: 42%
“…However, the outcome from group 3p + 1 is an exception since bandgap can even be enlarged (not reduced as in other semiconducting structures) under the effect of vertical electric fields. More interestingly, whereas transverse electric fields have been demonstrated to be more effective than vertical ones in BL-ZGNRs in terms of inducing larger bandgap, [27] here we show an inverse phenomenon, i.e., larger bandgap with vertical fields. In this present work, we consider BL-AGNRs in the presence of a transverse or/and a vertical electric field as schematized in Fig.…”
Section: Introductionsupporting
confidence: 42%
“…[14][15][16][17][18][19] It has shown that the bandgap in bilayer ribbon structures is strongly modulated under the impact of electric fields. [18,19] In bilayer zigzag graphene nanoribbons (BL-ZGNRs), [18] an energy gap up to 600 meV has been achieved in narrow ribbon structures and under the simultaneous influence of vertical and transverse electric fields. This bandgap induced by the presence of electric fields in BL-ZGNRs is much higher than that obtained by the same effect in 2D bilayer graphene sheets which is about 250 meV.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that in the BL-AGNR structure, the perpendicular electric field has a significant impact on tuning the bandgap of the material. On the other hand, the parallel electric field has a greater influence on the energy dispersion of zigzag bilayer graphene (Vũ & Trần, 2016;Vũ et al, 2017). Similar analytical calculations for each dimer line corresponding to each termination state have demonstrated that the maximum magnitudes of the gap are dissimilar for different critical potential strengths (Vũ & Trần, 2016;Vũ et al, 2017;Vũ et al, 2018).…”
Section: Introductionmentioning
confidence: 79%
“…In particular, the gap size for the armchair edge is Egap_max = 400 meV under the effect of |𝑉 𝑡 | = 0.96 V for M = 16 or Egap_max = 350 meV with |𝑉 𝑡 | = 1.3 V for M = 17 (Vũ et al, 2017). For the zigzag edge, the energy gaps of M = 16 and M = 19 have peaks of approximately 450 meV and 369 meV at |𝑉 𝑠 | = 1.14 V and |𝑉 𝑠 | = 0.92 V, respectively (Vũ & Trần, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation